Persamaan,Perbedaan,dan Pola Penggunaan Satuan Lingual yang Mengandung Pronomina Persona Pertama dan Kedua pada Teks Terjemahan Alquran dan Teks Terjemahan Hadis Sahih Buchori Muslim - Nugroho, Bahrudin Adi, Prof. Dr. Markhamah, M.Hum, Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2017)
This study has four purposes. (1) describes the equation of use the lingual unit containing personal pronouns of first and second person on TTA and TTH. (2) describes the difference of use the lingual unit containing personal pronouns first and second person on TTA and TTH. (3) describes the use patterns of the lingual unit containing personal pronouns in the first and second person on TTA. (4) describes the use patterns of the lingual unit containing personal pronouns in the first and second person on TTH. Type of this research is qualitative descriptive. This research subject is the translation text of the Quran and translation text of Hadith containing of language ethics. The object of this research is the lingual unit of PP I and PP II on the translation text of the Quran (TTA) and translation text of the Hadith (TTH) containing of language ethics. The data in this study is the clause containing lingual unit of PP I and II on TTA and TTH. Techniques of data collection are listening methods and log techniques. Data were analyzed using the method at the referential and agih method. The results showed (1) the equation of the lingual unit containing first pronouns discovered the category equation, function, and roles. As for the second pronouns was found the category equation, function, and roles. (2) the difference of the lingual unit containing first pronouns was found the difference category, function, and roles. The second pronouns was found the difference category, function, and roles. (3) The use pattern of the lingual unit of PP I and PP II on TTA was found as follows, on PP I was found the pattern of category change, the pattern of function, the pattern of role. As for PP II on TTA was found a pattern, a pattern change of category, pattern function, patterns of role. (4) The usage pattern of the lingual unit of PP I and II on TTH found as follows, on PP I was found the pattern of category change, the pattern of function, the pattern of role. PP II on TTA was found a pattern, a pattern change of category, the pattern of function, the pattern of role.